Architecture Information System With TOGAF-ADM (Case Study : Toko Sinar Remaja Maumere) - Darkel, Yohanes Brekmans M (Universitas Islam Raden Rahmat, Malang, 2026)
In the buying and selling industry, the development of information system technology allows sellers and buyers to interact with each other to achieve their respective goals and desires. The Sinar Teen Maumere light motorcycle spare parts store must also go through this process to develop a modified motorcycle spare parts business that can compete with other spare parts stores and manage the sales process systematically and computerized. Therefore, the purpose of this study is to develop a TOGAF ADM-based information system architecture for Sales and Inventory of the Sinar Teen Maumere Motorcycle Spare Parts Store. TOGAF has stages of preparation, Architectural Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solutions, and Architectural Change Management that can improve the performance and service of the Sinar Teen Store as well as control and monitor product sales. To produce a proposed application system design that can support business processes and create reports that occur at the Sinar Teen Motorcycle Spare Parts Store, the findings of this study provide a design that determines the business architecture, data architecture, application architecture, and technology architecture. At the general opportunities and solutions stage, a summary of all the sciences that produce the GAP analysis is explained as a reference for future information system development at the Sinar Teen Motor Spare Parts Store, Maumere.